Physical and psychological rehabilitation for common weightlifting injuries - Yang, Tang Xun; Wang, Wei; Kozlova, Elena; Oleshko, Valentin (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
In the process of weightlifting, there is an increased load on both the respiratory system, the cardiovascular system, and on individual parts of the nervous system. At the same time, special attention is paid to the possibilities of providing a stable body functioning after the cancellation of treatment course and the corresponding pharmacological support of athletes with treatment schedule or without it. The novelty of the study is determined by the need to ensure constant and stable work of the cardiovascular system. The authors note that this is possible both when the body performance indicators return to the level before injury, and in conditions of returning to original sports results. It is determined in the paper that the use of the instrumental model will make it possible to develop sustainable energy consumption and coordinate the balancing of loads on an athlete during the period of recovery after injury. Model formation is based on uniform signals in a correlated random process in a simulation model. The practical significance of the study is determined by the need to structure the training loads in the post-traumatic period. This reduces a number of physiological and psychological stresses on a person and allows increasing in the long term the loads that the athlete plans to utilise after returning to the sports sector.